HBV vaccination of HCV-infected patients with occult HBV infection and anti-HBc-positive blood donors - Pereira,J.S.F. (2006)
Anti-HBc positivity is a frequent cause of donation rejection at blood banks. Hepatitis B virus (HBV) infection may also occur in HBsAg-negative patients, a situation denoted occult infection. Similarly, very low levels of HBV-DNA have also been found in the sera of patients with chronic hepatitis C virus (HCV) infection, even in the absence of serum HBsAg. Initially we searched for HBV-DNA in serum of 100 blood donors and 50 HCV-infected patients who were HBsAg negative/anti-HBc positive by nested-PCR and by an HBV monitor commercial test for HBV-DNA. Anti-HBs seroconversion rates were measured in 100 blood donors and in 22 patients with chronic HCV infection after HBV vaccination to determine if the HBV vaccination could eliminate an occult HBV infection in these individuals. Occult HBV infection was detected in proportionally fewer blood donors (6/100 = 6%) than chronic hepatitis C patients (12/50 = 24%) (P < 0.05). We noted seroconversion in 6/6 (100%) HBV-DNA(+) and in 84/94 (89.4%) HBV-DNA(-) blood donors (P > 0.05). All subjects who were HBV-DNA(+) before the first dose of HBV vaccine (D1), became HBV-DNA(-) after D1, D2, and D3. Among 22 HCV-positive patients, 10 HBV-DNA(+) and 12 HBV-DNA(-), seroconversion was observed in 9/10 (90%) HBV-DNA(+) and in 9/12 (75%) HBV-DNA(-) subjects (P > 0.05). The disappearance of HBV-DNA in the majority of vaccinated patients suggests that residual HBV can be eliminated in patients with occult infection.